Jupiter's legacy. Volume 2 - Millar, Mark (Image Comics, Inc., 2020)
"By day, they are the world's greatest heroes. By night, they struggle with the same problems as the rest of us, and as the pressure increases on these super-celebrities, one of the team breaks away to become embroiled in the social unrest and political upheaval of America in the 1960s. You've never read a book like Jupiter's Legacy before, now a major Netflix Original series"--Publisher's website.